THE CAPABILITIES OF A REGISTER AS A QUALITY CONTROL OF THE PHARMACOTHERAPY IN OUTPATIENTS AT HIGH RISK OF CARDIOVASCULAR COMPLICATIONS (THE "LIS-1" REGISTER) - M. L. Ginzburg; S. Y. Martsevich; N. P. Kutishenko; Y. V. Lukina; A. D. Deev (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the frequency of the prescription of cardiovascular drugs in patients before the reference acute myocardial infarction (AMI) based on the register "LIS-1" (Lubertsy mortality study of patients after myocardial infarction).Material and methods. Stage 1: development of the Register of patients with AMI admitted to cardiology departments of hospitals in Luberets district, Moscow region (2005-2007) and discharged for outpatient treatment. Median follow-up – 1.6 years (1.0, 2.4). The primary endpoint – total mortality. Stage 2: the continuation of register "LIS-1" (2011-2012).Results.1133 patients (mean age of men 60.1±0.5, women – 71.4±0.4 years) were included in the 1st stage of the study; 172 (15.2%) died in the hospital. Before the reference hospitalization 21.4% of patients had been receiving b-blockers, 35.3% - renin-angiotensin-aldosterone system (RAAS) inhibitors, 15.7% - antiplatelet agents, 1.9% - statins, 13% of patients - diuretics. Statistically significant (adjusted for sex and age) positive impact on hospital mortality reduction had a treatment with b-blockers [OR=0.542, CI=0.357-0.824, p=0.004] and RAAS inhibitors [OR=0.710; CI=0.512-0.986, p=0.040] prior to the development of acute myocardial infarction. As the number of patients receiving statins and antiplatelet agents was small, the contribution these drugs intake on hospital mortality was not identified. 272 patients (mean age 63.6±12.6 years) were included on the second phase of the study. The information about the received therapy before reference hospitalization was reported by 173 patients: 39% of patients used b-blockers, 47% - RAAS inhibitors, 37% - antiplatelet agents, 15% - statins, 15% of patients - diuretics. Positive changes in the frequency of the prescription of essential drugs were observed in 5 years: a significant increase in number of patients with b-blockers (p<0.001), RAAS inhibitors (p<0.01), antiplatelet agents (p<0.05) and statins (p<0.001). The number of patients with diuretics did not significantly change.Conclusion. The Register "LIS-1" (Lubertsy study of mortality in patients after myocardial infarction) allowed not only to assess data on clinical practice at a certain period, but also to evaluate the changes in drug therapy of patients with high and very high cardiovascular risk.